Firm innovation in the Asia and Pacific region: the role of governance environment, firm characteristics, and external finance. (29th March 2019) - Abumousa, Ashraf
This paper investigates the impact of the governance environment, firm characteristics, and external finance on firm innovation. Cross-sectional data from World Bank Enterprise Survey (WBES) for the year 2015 were adopted to examine this influence in 4, 993 firms across seven countries from East Asia and the Pacific region. While several aspects of innovation have been identified in innovation research, this paper defines firm innovation broadly to comprise the introduction of new production outputs, investment activities, and the effectiveness of innovative outputs . Further, the paper assesses the innovating firms' performance based on their prevailed business environment. The results show that firms can innovate even in the weak court system. Firms that pay bribes to public officials are more innovative. The paper also finds a significant association between some firm characteristics and innovation. Findings suggest that external finance promotes innovation better than internal finance.